Fecundity and fertility in a freshwater population of the neotropical amphidromous shrimp Macrobrachium acanthurus from the southeastern Atlantic - Bertini, Giovana [UNESP]; Antonio Baeza, J. (Taylor & Francis Ltd, 2014)
The neotropical amphidromous shrimp Macrobrachium acanthurus is one of various freshwater crustaceans heavily exploited in the southwestern Atlantic. Fecundity (n degrees early embryos female(-1)) was examined during 2007 at four different localities (Iguape, Registro, Sete Barras, and Eldorado) along a stretch of river extending over 85 km (Ribeira de Iguape, Sao Paulo State, Brazil). Also, fertility (n degrees hatched larvae female(-1)) was examined at one locality (Registro) during 2009-2010. Fecundity (mean +/- SD: 5191 +/- 2635; range: 1086-13,014 embryos female(-1)) did not vary throughout the segment of river studied. Fecundity increased with female body size (carapace length, CL). However, fecundity scaled negatively with shrimp body size; females produce disproportionably fewer eggs with a unit increase in CL. The conditions explaining the negative allometric relationship between fecundity and female body size in M. acanthurus remain to be addressed. Nevertheless, natural food constraints limiting the ability of large but not small females to acquire enough resources to produce and fill their gonads with oocytes represents a plausible explanation for the negative scaling of fecundity with body size. Fertility varied between 545 and 12,465 hatched larvae female(-1) with an average (+/- SD) of 3981 (+/- 2693) and increased isometrically with a unit increase in female body size. M. acanthurus has an average fecundity and fertility that represents one of the extremes regarding the trade-off between fecundity/fertility and egg-size reported for caridean shrimps. All of this information needs to be considered in assessing shrimp stocks and establishing a sustainable management plan for this exploited species in the southwestern Atlantic.
Keywords: freshwater prawn; reproduction; scaling; allometry; exploited species